Reconstructing Qur’anic Economic Principles through a Tafsīr Maqāṣidī Approach - Mimin Mintarsih; Oyo Sunaryo Muklas; Burhanuddin; Asep Abdul Halim; Nyimas Ai Gantini (STAI Al-Mas'udiyah, 2026)
Islamic economics scholarship has often been framed through a normative–fiqh orientation that emphasizes legal compliance and economic instruments, while the purposive and ethical vision of the Qur’an remains under-theorized. This article reconstructs Qur’anic economic principles through a tafsīr maqāṣidī approach by positioning maqāṣid al-sharī‘ah as the principal hermeneutical lens for interpreting economic verses. Using qualitative library research, the study combines thematic exegesis (tafsīr mawḍū‘ī) with maqāṣidī analysis of verses concerning wealth circulation, distributive justice, the prohibition of exploitation, social responsibility, and the protection of vulnerable groups. Verses were selected on the basis of two criteria: direct relevance to the acquisition, circulation, and protection of wealth, and indirect relevance to the ethical objectives that govern economic life. The study finds that a maqāṣidī reading produces a coherent framework of Qur’anic economics centered on distributive justice, anti-exploitation, ethical production, the protection of human dignity, sustainability, and the balance between private rights and public welfare. The article argues that tafsīr maqāṣidī is not only an interpretive method but also a conceptual foundation for Islamic economics that is theoretically distinct from conventional economics and responsive to contemporary socio-economic challenges.